Topology-dependent self-structure mediation and efficient energy conversion in heat-flux-driven rotors of cholesteric droplets - Jun Yoshioka (Nature Portfolio, 2018)
The Lehmann effect describes the spontaneous rotation of cholesteric liquid crystals in response to heat input. Here, the authors stabilise it by dispersing cholesteric droplets into a poorly miscible solvent and show dependences of rotation speed and conversion efficiency on the topological states.